KESESUAIAN PERMENKOMINFO NOMOR 05 TAHUN 2020 DENGAN PRINSIP KEBEBASAN BERPENDAPAT DAN BEREKSPRESI DALAM HAK ASASI MANUSIA - Rahardjo, Ridho Dwi; Afifah, Wiwik (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The current government can block Electronic System Operators through Regulation of the Minister of Communication and Information Number 5 of 2020 concerning Private Scope Electronic System Operators. However, this regulation does not regulate in detail. This study aims to find things that must be done whether they are in line with the principles of freedom and expression. By going through a normative approach method with the aim of answering issues based on the scientific side. The results of this study indicate that Permenkominfo No. 5 of 2020 is not in accordance with the principle of freedom of opinion and expression because the regulation related to the phrase "disturbing" does not have detailed indicators. So that if the government considers content to be troubling, the government can take repressive measures. Meanwhile, the troubling indicators in this regulation have not yet been developed. This is because freedom of expression and opinion is protected by applicable laws and cannot be contested. And it is necessary to look for new things related to the government's efforts to monitor and provide legal protection for personal data or privacy without limiting the rights of every citizen